PENGARUH MEDIA PEMBELAJARAN PhET DI KELAS 6 UPTD SDN TANJUNG JATI 2 - H, Jeki Aprisela; Saputra, Andra; Solihin, Ahmad (Universitas Trunojoyo Madura, 2024)
Elementary school students' ability to focus and concentrate is crucial for success in the learning process. However, fine arts learning at SDN 13 West Padang Panjang remains dominated by conventional methods such as free drawing, which are less effective in optimizing student focus. This research aims to test the effectiveness of the collage craft method in enhancing students' focus and concentration. Using a Quasi Experimental Design with a Nonequivalent Control Group Design, the study was conducted on September 18 and November 20, 2024, involving all fifth-grade students in the 2024/2025 academic year as the sample. A saturated sampling technique was used, including the entire population. Data collection methods included observation, documentation, and tests. Data analysis included normality, homogeneity, and t-tests using SPSS 21 for accurate results. The findings indicated a significant increase in focus and concentration among students using the collage craft method compared to those using free drawing, with a tcount value of 3.097, greater than ttable 1.685, thus supporting the alternative hypothesis. These findings support collage craft as an effective method for increasing student engagement and concentration in fine arts learning.